OUR FUNDAMENTAL PHYSICAL SPACE: AN ESSAY ON THE METAPHYSICS OF THE WAVE FUNCTION. - KEMING CHEN, EDDY (Journal of Philosophy, 2017)
The article focuses on a study for analysis of metaphysics related to quantum wave functions along with its involvement in determination of fundamental physical space. Topics discussed include usage of quantum state as reference of physical object with wave function description; assessment of different conditions such as wave function realism along with configuration space realism; and comparison of probability density function with transport equation.